Morphological and morphometrical study of placenta in normal and hypertensive pregnancies - Pushpa Gowda; K S Jayanthi (Wolters Kluwer Medknow Publications, 2014)
Background and Aim: Placenta is the main channel in utero, through which the fetus receives its nutrition from the mother. Hypertensive disorders of pregnancy are fairly common and affect the growth and development of the placenta and fetus in many ways. Knowledge of these changes in placenta due to hypertension in pregnancy is essential as many of these changes can be diagnosed prenatally by available techniques to improve the fetal outcome and reduce perinatal morbidity and mortality. Materials and Methods: The present study was conducted to note the morphometrical and morphological parameters in the placenta of normal and hypertensive pregnancies and to correlate them with fetal outcome. The study was done on 30 placentae as control group, obtained after delivery of normotensive women and 30 placentae as study group, which were obtained after delivery of hypertensive mothers which included chronic hypertension, pre eclampsia and eclampsia. The placental specimens were collected from the department of obstetrics and gynecology, KIMS, Bangalore and new born parameters were taken from their records. Results: The placental morphometrical parameters were significantly less in hypertensive group as compared to the control group. The mean placental weight was 458.33± 70.47gms; mean placental surface area was 215.82±27.83 sqcms, the mean placental volume was 583.67+66.21cc and mean decidual thickness was 2.50 ±0.24 cms in hypertensive group while in the control group the values were 561.67±77.33 gms, 241.91±37.23 sqcms, 674.00±88.50 cc and 2.83±0.34 cms respectively. The mean birth weight (kg) of newborn was 2.92 ± 0.45 in control group and it was and 2.47 ±0.40 in hypertensive group. Conclusion: Thus hypertensive disorders of pregnancy affects the placenta in a major way by decreasing its weight, surface area, thickness and volume and by increasing pathological changes like placental infarcts and calcified areas which adversely affect fetal parameters like weight and APGAR score.